Morphology and phylogenetic analysis of two new species of deep-sea golden gorgonians (Cnidaria: Octocorallia: Chrysogorgiidae) from seamounts in the Western Pacific Ocean - Xu, Yu; Zhan, Zifeng; Li, Yang; Xu, Kuidong (Zootaxa, 2020)
Two new species of deep-sea chrysogorgiid gorgonians are described from the tropical Western Pacific: Iridogorgia densispicula n. sp. from an unnamed seamount in the Caroline Plate with water depth of 1204 m and Iridogorgia squarrosa n. sp. from an unnamed seamount near the Mariana Trench with water depth of 1458 m. Iridogorgia densispicula n. sp. has a slender stem with bud-like polyps, dense sclerites in polyps and branches, spindle-like scales in polyp bases, and long rods in tentacles. Iridogorgia squarrosa n. sp. has a brown to nearly black axis, large polyps with eight obvious columns, elongated scales in the back of tentacles, and special scales at base of polyps with many sculptures. By the combination of these features, the two new species differ distinctly from each other and all other congeners. Phylogenetic analyses indicate that I. densispicula n. sp. is sister to all other Iridogorgia Verrill, 1883, while I. squarrosa n. sp. showed close relationship with I. splendens Watling, 2007.